Contrastive Analysis: Intentional Modality of Indonesian and Japanese - Eman Suherman (Journal of Japanese Language Education and Linguistics, 2023)
The objective of this study is to provide a comprehensive description of the modality of Indonesian Intentional and Japanese Intentional modality. Intentional modality refers to a linguistic modality that is employed to convey expressions of desire, hope, request, or requirement. The Indonesian intentional modality and Japanese intentional modality exhibit numerous distinctions, which can pose challenges for learners of both languages. The next section provides an overview of the backdrop for this research study. This study employed a descriptive methodology to systematically examine data in order to identify and delineate similarities and differences between the two variables. The intentional modality data for the Indonesian language was obtained from Indonesian language textbooks designed for elementary level I and II foreign speakers, which were published by INCULS, Faculty of Humanities, Gadjah Mada University. Similarly, the intentional modality data for the Japanese language was extracted from the books titled "Minna No Nihongo Shokyuu I and II."